(untitled) (MAUSAM, 1984)
During break periods in the southwest monsoon season in the semi-arid environment of India, crops under rainfed as well as irrigated conditions are prone to the effect of "atmospheric drought" as distinguished from ’soil’ or "agricultural drought". This situation occurring at different stages of crop growth for a week or two is not reflected in the soil water balance, but is revealed in the crop growth rates and yields. Evidence exists of energy gain through advection by evaporating surfaces of the order of 4 to 5 mm/day resulting in an increase in potential evapotranspiration rates by 2-3 mm/day. This situation can be traced on a macroscale to the westerlies during the ’break periods’ and on a local scale to the post monsoon warming of surroundings with a reduces intensity. As yet, apart from the soil budgeting approach with the limitation mentioned above, there appears to be no method by which years with widely varying amounts of total seasonal rainfall but with different distribution patterns in the different growth stages resulting in atmospheric drought could be distinguished from one another or grouped together. This paper while focussing the attention to this aspect illustrates an empirical technique based on sequential dry days for assessment of atmospheric drought.